The sesquiterpene lactone dehydroleucodine triggers senescence and apoptosis in association with accumulation of DNA damage markers - Costantino, Valeria Victoria (2013)
Sesquiterpene lactones (SLs) are plant-derived compounds that display anti-cancer effects. Some SLs derivatives have a marked killing effect on cancer cells and have therefore reached clinical trials. Little is known regarding the mechanism of action of SLs. We studied the responses of human cancer cells exposed to various concentrations of dehydroleucodine (DhL), a SL of the guaianolide group isolated and purified from Artemisia douglasiana (Besser), a medicinal herb that is commonly used in Argentina. We demonstrate for the first time that treatment of cancer cells with DhL, promotes the accumulation of DNA damage markers such as phosphorylation of ATM and focal organization of cH2AX and 53BP1. This accumulation triggers cell senescence or apoptosis depending on the concentration of the DhL delivered to cells. Transient DhL treatment also induces marked accumulation of senescent cells. Our findings help elucidate the mechanism whereby DhL triggers cell cycle arrest and cell death and provide a basis for further exploration of the effects of DhL in in vivo cancer treatment models.